An Overview of the Readiness of Regional General Hospital Infrastructure (RSUD) Karanganyar Regency in Implementing the National Health Insurance Standard Inpatient Classes - Rizky, Wahyu; Afriyanto, Dzul Fahmi; Shoffiyatunisaak, N.A (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hospitals are increasingly faced with the challenge of providing quality services to patients, having to meet accreditation requirement, patient needs and expectations, social and ethical values, demands for continuous improvement in the quality of health services, as well as reducing costs, so that local people continue to use health services and facilities in that country. The aim of the research is to determine the readiness of the (RSUD) Rumah Sakit Umum Daerah Kabupaten Karanganyar infrastructure in implementing standard national health insurance inpatient classes. Qualitative research with a case study approach. The population in this study was Hospital Management. Sampling uses purposive sampling. The results of research on the application of KRIS are generally known, but do not know specifically because they have never received direct socialization and there are no regulations that specifically guide KRIS. sufficient to face the current situation, and management and work realization have attempted to provide the best infrastructure for patients and in accordance with established standards. RSUD Kabupaten Karanganyar is ready if KRIS has to be implemented. This is supported by the readiness of infrastructure at the RSUD Kabupaten Karanganyar which has begun to be prepared in accordance with the KRIS Criteria standards and has good bed management.